Investigation on the quality of bio-oil produced through fast pyrolysis of biomass-polymer waste mixture - Seyed, Amirmostafa Jourabchi; Ng, H. K; Gan, S.; Yap, Z. Y (IOP Publishing, 2016)
A high-impact poly-styrene (HIPS) was mixed with dried and ground coconut shell (CS) at equal weight percentage. Fast pyrolysis was carried out on the mixture in a fixed bed reactor over a temperature range of 573 K to 1073 K, and a nitrogen (N2) linear velocity range of 7.8x10-5 m/s to 6.7x10-2 m/s to produce bio-oil. Heat transfer and fluid dynamics of the pyrolysis process inside the reactor was visualised by using Computational Fluid Dynamics (CFD). The CFD modelling was validated by experimental results and they both indicated that at temperature of 923 K and N2 linear velocity of 7.8x10-5 m/s, the maximum bio-oil yield of 52.02 wt% is achieved.